Dendrimers in Oral Drug Delivery Application: Current Explorations, Toxicity Issues and Strategies for Improvement - Liu, Yuanjie; K. Tee, Jie; N. C. Chiu, Gigi (Current Pharmaceutical Design, 2015)
Dendrimers are emerging as potential novel nano-scaled material in drug delivery applications. An interesting area of application is oral drug delivery. In oral drug delivery, many drugs suffer from low bioavailability due to the presence of various biological barriers. Dendrimers have been shown to modulate tight junctions and the integrity of cellular membranes. This effect gives hope for dendrimer to be applied in oral drug delivery. Based on such properties, dendrimers are further surface-modified so that the system will be more suitable for oral delivery applications. Cationic dendrimers are commonly conjugated with neutral or negatively charged ligands, such as polyethylene glycol (PEG), to reduce potential toxicity in gastrointestinal (G.I.) tract. Dendrimers are also surfacemodified to inhibit the efflux effect of P-glycoprotein, which is one of the major drug efflux pumps in G.I. tract. Another interesting strategy is to directly conjugate or mix dendrimer with drugs either to form a dendrimer-drug conjugation or complex to deliver the drug. In this review, application of dendrimers in oral drug delivery will be discussed. The main focus is on the various surface modification strategies to design a more desirable dendrimer-based delivery system that fits the need in oral drug delivery.
Keywords: bioavailability